Diversity and plant growth promotion potential of endophytic fungi isolated from hairy vetch in Japan - Taheri, Parisa; Dastogeer, Khondoker M. G.; Ratu, Safirah Tasa Nerves; Agyekum, Dominic V. A.; Yasuda, Michiko; Fujii, Yoshiharu; Okazaki, Shin (Frontiers in Plant Science, 2024)
Hairy vetch (Vicia villosa Roth), a leguminous plant with nitrogen-fixing ability, is used as a cover crop and has the potential to suppress weeds and plant diseases. The microbial composition, particularly fungal endophytes, which may be related to the beneficial functions of this crop, has not been previously studied. In this study, we analyzed the diversity and function of culturable fungal endophytes associated with hairy vetch from eight locations across Japan. Using the fungal culture method, a total of 2,186 isolates were recovered and assigned to 80 distinct internal transcribed spacer (ITS) genotypes, spanning 28 genera. The results demonstrated that geographic location and soil physicochemical properties significantly influence the community composition of the hairy vetch fungal endophytes. Soil pH showed a significant positive correlation with the abundance of Penicillium, which was the most dominant genus in all the sampling locations and tissues. The majority of the isolates promoted plant growth and colonized hairy vetch and soybean roots, significantly promoting the growth of hairy vetch and/or soybean plants. Among the isolates, Penicillium griseofulvum AKL25 and Trichoderma koningii AKR15 significantly enhanced both hairy vetch and soybean growth, respectively. Meanwhile, Alternaria alternata OGL80 significantly increased soybean growth, but it did not affect hairy vetch growth, indicating host specificity of the fungal endophytes. In conclusion, this study showed that soil properties and geographic location play a critical role in shaping the community composition and structure of endophytic fungi associated with hairy vetch. Additionally, the isolated fungi promoted hairy vetch and soybean growth, with a host preference. Furthermore, this study revealed that a novel endophytic fungus, P. griseofulvum AKL25, which has high growth-promoting activity, can be utilized as a microbial inoculant to promote hairy vetch and soybean growth in sustainable agriculture.